2022
DOI: 10.3390/atmos13101669
|View full text |Cite
|
Sign up to set email alerts
|

Precoating Effects in Fine Steelmaking Dust Filtration

Abstract: Particle emissions into the atmosphere can cause extensive damage to the environment and human health. To improve the efficiency in the collection of submicronic particles, new filtration media appeared on the market due to new textile technologies and equipment, such as filter media developed with polytetrafluoroethylene (PTFE) membranes; however, these are more expensive. A filter coating technique called precoating is a more economical alternative that could enhance filtration efficiency. This paper aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Excessively large precoating particles can decrease the regeneration efficiency. Andrade et al 13 studied the influence of precoating on the filtration duration of filters for steelmaking dust and found that precoating reduced the frequency of cleaning within a certain period. The precoated filter exhibited a filtration duration thrice that of the unprecoated filter, thereby extending the service life.…”
Section: Introductionmentioning
confidence: 99%
“…Excessively large precoating particles can decrease the regeneration efficiency. Andrade et al 13 studied the influence of precoating on the filtration duration of filters for steelmaking dust and found that precoating reduced the frequency of cleaning within a certain period. The precoated filter exhibited a filtration duration thrice that of the unprecoated filter, thereby extending the service life.…”
Section: Introductionmentioning
confidence: 99%